Silver‐coated monolithic columns for separation in radiopharmaceutical applications. Issue 7 (27th February 2014) - Sedlacek, Ondrej; Kucka, Jan; Svec, Frantisek; Hruby, Martin
<x xml:space="preserve">Abstract</x> In this study, we demonstrate the preparation of a macroporous monolithic column containing anchored silver nanoparticles and its use for the elimination of excess radioiodine from the radiolabeled pharmaceutical. The poly(glycidyl methacrylate‐co‐ethylene dimethacrylate) monolith was first functionalized with cystamine and the free thiol groups liberated by reaction with borohydride. In‐house‐prepared silver nanoparticles were then attached by interaction with the surface thiols. The deiodization process was demonstrated with the commonly used radiopharmaceutical m‐iodobenzylguanidine labeled with radionuclide iodine‐125.